603. Multi-morbidity and Impaired CD4/CD8 Ratios in Older Adults with Well-Controlled HIV. (26th November 2018) - Adeyemi, Oluwatoyin; Diep, Lisa
Abstract: Background: Older age has been associated with impaired CD4 recovery and a low CD4:CD8 ratio is an independent predictor of non-AIDS morbidity/mortality. In this study we describe the overall comorbidity burden and assess factors associated with CD4:CD8 <1 among HIV+ older adults 60 years+ seen at CORE Center, Cook County Health and Hospital System; a safety-net health system. Methods: We evaluated demographic, clinical, and lab variables in all HIV+> 60 years who had at least 1 primary care visit from January 1, 2016 to May 31, 2017 at the RMR CORE center. Since HIV viremia is associated with CD4 recovery, analysis on CD4:CD8 ratios was restricted to the patients with viral suppression. Results: There were 809 patients with a median age of 63 (range: 60–89) years. Seventy-five percent were male, 74% black, 17% Hispanic and 8% white. Mean CD4 was 538 (+307) cells/mm; 107 (13%) had CD4 < 200 and 675 (84%) had undetectable HIVRNA (<40 copies/mL). 38% were HCV Ab+. Common comorbidities were hypertension 62%, COPD 23%, diabetes 22%, depression 17%, osteoarthritis 15%, neuropathy, chronic kidney disease (CKD) and coronary artery disease (CAD) 13% each. 50% had 1–2 comorbidities and 31% had >3 co-morbidities. Of the 675 patients with suppressed viremia, 470 patient (70%) had CD4:CD8 <1 and 245 (36%) had CD4:CD8 <0.5. Compared with patients with CD4:CD8 >1, patient with CD4:CD8 <1 had lower CD4 counts (451 vs. 739 cells/mm 3 ; P < 0.001), were less likely to have CD4 > 500 (35% vs. 75%; P < 0.001), more likely to have CD4 <200 (13% vs. 1%; P < 0.001), be male (82% vs. 60%; P < 0.001), HCVab+ (39% vs. 32%; P 0.05). They also trended to have more CAD 7% vs. 4% ( P = 0.1) and more CKD 15% vs. 11% ( P = 0.2). Conclusion: There was a high rate of multi-morbidity among older, predominantly ethnic minorities HIV-infected adults with 56% having >2 comorbidities. In the setting of viral suppression, 70% still had a CD4:CD8 ratio <1 which likely reflects the effects of older age, and lower CD4 nadir. This impaired immune restoration and co-morbidity burden portend a higher risk of non-AIDS morbidity and mortality in these patients and highlights the need for comprehensive care in HIV clinic settings. Disclosures: All authors: No reported disclosures.